The financial motivation to keep information secure. Issue 2 (February 2020) - Stremlau, Thorsten
Abstract : The number one driver of the cyber security industry right now is the global push to digitally transform businesses. As a result, the way that companies need to protect their data and assets is changing and the security challenges they are facing are often situations with which they have very little experience.